Methodical Approaches to Technique's Formation of Performance in Beethoven's Piano Style - Yulia Tarchyns’ka (Pedagogical Discourse, 2011)
The issues of piano performing skills' rational formation are highlighted in the article as conscious mastering of their co-creative and interdependent components; the content of performance's methods are defined, mastering of which creates conditions for effective technical preparation of a performer; the examples of their important mastering in Beethoven's piano style are given.